CT-MRI Image Fusion-Based Computer-Assisted Navigation Management of Communicative Tumors Involved the Infratemporal-Middle Cranial Fossa - Yang, Rong; Lu, Han; Wang, Yang; Peng, Xin; Mao, Chi; Yi, Zhiqiang; Guo, Yuxing; Guo, Chuanbin (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Computed tomography (CT) and magnetic resonance imaging (MRI) are crucial for preoperative assessment of the three-dimensional (3D) spatial position relationships of tumor, vital vessels, brain tissue, and craniomaxillofacial bones precisely. The value of CT-MRI-based image fusion was explored for the preoperative assessment, virtual planning, and navigation surgery application during the treatment of communicative tumors involved the infratemporal fossa (ITF) and middle cranial fossa.Methods Eight patients with infratemporal-middle cranial fossa communicative tumors (ICFCTs) were enrolled in this retrospective study. Plain CT, contrast CT, and MRI image data were imported into a workstation for image fusion, which were used for 3D image reconstruction, virtual surgical planning, and intraoperative navigation sequentially. Therapeutic effect was evaluated through the clinical data analysis of ICFCT patients after CT-MRI image fusion-based navigation-guided biopsy or surgery.Results High-quality CT-MRI image fusion and 3D reconstruction were obtained in all eight cases. Image fusion combined with 3D image reconstruction enhanced the preoperative assessment of ICFCT, and improved the surgical performance via virtual planning. Definite pathological diagnosis was obtained in all four navigation-guided core needle biopsies. Complete removal of the tumor was achieved with one exception among the seven navigation-guided operations. Postoperative cerebrospinal fluid leakage occurred in one patient with recurrent meningioma.Conclusion CT-MRI image fusion combined with computer-assisted navigation management, optimized the accuracy, safety, and surgical results for core needle biopsy and surgery of ICFCTs.
Keywords: CT; MRI; image fusion; computer-aided navigation; infratemporal-middle cranial fossa; tumor